(untitled) (Research, Society and Development, 2021)
This article aims to discuss digital literacy in elementary school 1, considering the proposal of the Common National Curricular Base, particularly the linguistic/semiotic analysis. Specifically, to examine the generative path of meaning in the fundamental, narrative and discursive levels of the production of multisemiotic text, the meme, of 3rd grade students. Therefore, the question was asked whether 3rd grade students are being encouraged by the school to develop meaningful skills in the language practices of multisemiotic texts such as the digital genre meme. In response it is assumed that 3rd grade students, who can already be considered digital natives, comment on the content and even produce memes, because they are already being trained by the school to develop critical and reflective sense regarding the language practices of multisemiotic texts such as the meme. We adopted the axis of linguistic/semiotic analysis of the Common Curricular Base (2018), in the processes of reading and production of texts (oral, written, and multisemiotic), with Fiorin (2017), Soares (1998), and Ribeiro (2018) as theoretical support.